Aqueous Zinc Ion Batteries: Controlling Vanadate Nanofiber Interlayer via Intercalation with Conducting Polymers: Cathode Material Design for Rechargeable Aqueous Zinc Ion Batteries (Adv. Funct. Mater. 26/2021). (24th June 2021) - Kim, Jichang; Lee, Se Hun; Park, Changyong; Kim, Hyung‐Seok; Park, Jae‐Ho; Chung, Kyung Yoon; Ahn, Heejoon
Abstract : In article number 2100005, Heejoon Ahn and co‐workers report a facile sonochemical method for creating oxygen vacancies and controlling the interlayer of an ammonium vanadate nanofiber (AVNF) crystal by intercalating poly(3, 4‐ethylenedioxythiophene) into the vanadate lattice, which can improve the rate capability and electrochemical reversibility as well as the cycle stability of AVNF as a cathode material for aqueous zinc‐ion batteries.